NURSING CARE OF CHILDREN WITH FEBRILE CONVULSION WITH HYPERTHERMIY NURSING PROBLEMS IN SRIKANDI ROOM JOMBANG HOSPITAL - Nurul Azizah; Faishol Roni; H.Arif Wijaya; H.Imam Fatoni; Achmad Wahdi (Universitas STRADA Indonesia, 2023)
Background : Febrile seizures are disorders that arise due to an abnormal increase in body temperature (> 38 0 C). Febrile seizures are often associated with epilepsy and the risk of mental retardation in children. Method : The design of this research is a case study using the subject of 2 pediatric patients who experienced febrile seizures with hyperthermia nursing problems on the first day, nursing care was carried out 3 consecutive days by providing warm compresses or tepid sponge interventions. Results : The results showed the problem of hyperthermia with warm compresses or a tepid sponge, the problem was resolved in reducing the increase in body temperature. Analysis : To carry out nursing care for clients who experience febrile seizures with priority problems of hyperthermia. Conclution : Warm compresses or tepid sponges can be used in hospitals as additional therapy to lower body temperature.